2016
DOI: 10.1039/c6cc05439k
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of figure-of-eight helical bisBODIPY macrocycles and their chiroptical properties

Abstract: A macrocyclic bisBODIPY (bis(boron-dipyrromethene)) complex [1B2] with a figure-of-eight helicity was synthesized and successfully resolved. [1B2] was proven to be one of the most efficient red-emitting CPL (circularly polarized luminescence) fluorophores reported to date (λ = 663 nm, |glum| = 9 × 10(-3), ΦF = 0.58).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 33 publications
0
43
0
Order By: Relevance
“…However, despite the fact that several BODIPY‐based chiral architectures were found to show significant CPL effects, azabora[ n ]helicenes, that incorporate boron directly in the helical architecture, were reported only in a single work so far . These systems build on borylated arylpyridine N,C‐chelates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the fact that several BODIPY‐based chiral architectures were found to show significant CPL effects, azabora[ n ]helicenes, that incorporate boron directly in the helical architecture, were reported only in a single work so far . These systems build on borylated arylpyridine N,C‐chelates.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30,[41][42][43][44][45][46] Helicenes belongtothe most frequently reported CPL-SOM architectures, amongt hem carbo[n]helicenes, [33,[47][48][49][50][51] helicenes that incorporate heteroatoms (azahelicenes, [52][53][54][55] oxahelicenes, [34,54] thiahelicenes), [56] and metallahelicenes. [57,58] However,d espite the factt hat several BODIPY-basedc hiral architectures were found to show significant CPL effects, [39,46,[59][60][61][62][63][64] azabora [n]helicenes, that incorporate boron directly in the helical architecture, were reported only in as ingle work so far. [65] These systemsb uild on borylated arylpyridine N,C-chelates.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in the disclosure of several CPL‐SOM systems described as either axially or helically chiral BODIPYs in which the fluorophore core has been asymmetrically perturbed through the introduction of either covalent or steric restraints. However, despite these advances in homochiral BODIPY design, their CPL quantum efficiencies are still limited by low luminescence dissymmetry factors (highest reported | g lum | equal to 4.7×10 −3 or 9×10 −3 for monomeric or dimeric homochiral BODIPYs, respectively,). Future improvement of these | g lum | values will require an improved understanding of the link between | g lum | and molecular structure in the helically chiral BODIPY series.…”
Section: Introductionmentioning
confidence: 99%
“…The Nabeshimag roup developed ad imeric compound (6) containing two N 2 O 2 pockets to further exploit helical chirality in dipyrrin-based boron complexes. [2] Reaction of 6 with excess phenylboronic acid afforded complex 7, which featured a figure-of-eight helical structure due to boron's propensity to adopt at etrahedral geometry ( Figure 2). Ther acemic solidstate structure of 7 confirmed that each of the N 2 O 2 3À dipyrrinate moieties adopt the same helical chirality (i.e., P, P -o rM,Misomers).…”
Section: Chiral Luminescent Materialsmentioning
confidence: 99%
“…In this concept article, we focus on selectede xamples of group 13 complexes of N 2 O 2 nÀ ligands with unusual chirality, [1,2] sensing/detection capabilities, [3][4][5][6][7][8][9][10][11] utility in organic electronics, [12][13][14][15] and redox activity. [16,17] The use of N 2 O 2 nÀ ligands in main group coordination chemistry affords opportunitiestoexploit the chelate effect, and often results in the production of stable and robust complexes.T he addition of nitrogen/oxygen atoms to p-conjugated ligands can lead to extended electronic delocalization and stabilized frontier orbitals in the resulting complexes.G roup 13 elements are advantageous in this context as they can promote rigidity and induce chirality when coordinated to N 2 O 2 nÀ ligandsv ia strong covalent bonds to oxygen and nitrogen.…”
Section: Introductionmentioning
confidence: 99%